Acculturation of Java and Chinese Culture in Historical Perspective - M Bagus Sekar Alam (Sinolingua: Journal of Chinese Studies, 2023)
The purpose of this study is to explain historically the acculturation process of Javanese-Chinese culture which its existence is still being felt today. The research question is how was the process of acculturation of Javanese and Chinese culture and what form. The method used in this study is the historical method which has four operational steps: Heuristics, criticism, interpretation,  and historiography. A search for library research is needed to find out initial information on the problems being studied. Anthropological and sociological approaches are needed to sharpen data analysis. The results of this study explain that the acculturation of Javanese and Chinese culture was formed through a long historical process since the 5th century AD. The initial interaction of ethnic Chinese with Javanese people took place intensively through trade relations. The arrival of ethnic Chinese to Java took place gradually by sea. The interaction of ethnic Chinese culture with the local community runs naturally and without any cultural conflict between the two. This long-standing cultural interaction has resulted in the acculturation of Javanese and Chinese cultures merging into one local culture of the Javanese people. Almost all elements of Javanese life are more or less influenced by Chinese culture. As in architecture, food, literature, batik, sports, musical instruments, religion, performing arts and traditions. The conclusion of this study shows that the process of acculturation of Javanese and Chinese cultures has given birth to a mixed culture that has become part of the cultural wealth of Javanese society.